Fruits and vegetables market in Romania: Better understand consumers' preferences - Raluca Andreea Ion (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Fruits and vegetables are important for maintaining the human health, and, thus, they are present in everyday consumers' basket. They are seasonable and perishable products and, as a result, they need to be processed and transformed into cans and preserved products. The objective of this research is to identify the main directions of developing the sector of preserved fruits and vegetables products. Pursuing this, a survey was carried out, for collecting data about consumers' buying behaviour, their preferences for preserved fruits and vegetable, buying frequency and budgets spent for these products, on average, per month. Research findings show that over 94 per cent of respondents consume preserved vegetables and fruits. Among preserved vegetables, broth, tomato juice, pickles and frozen vegetables are consumed frequently. As regards preserved fruits, apples / pears juice is consumed more often than other products. The most important criteria for choosing canned vegetables and fruits products are composition, taste and origin. These results are useful for better understand consumers' behaviour of buying processed vegetables and fruits and to decide, further on, the directions of developing food processing industry for vegetables and fruits.
Keywords: 330; Preserved fruits; preserved vegetables; survey; consumer behaviour